2009
DOI: 10.1074/jbc.m109.062414
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Inhibitory Amino Acid Transporter Is a Cl−/γ-Aminobutyrate Co-transporter

Abstract: The vesicular inhibitory amino acid transporter (VIAAT) is a synaptic vesicle protein responsible for the vesicular storage of ␥-aminobutyrate (GABA) and glycine which plays an essential role in GABAergic and glycinergic neurotransmission. The transport mechanism of VIAAT remains largely unknown. Here, we show that proteoliposomes containing purified VIAAT actively took up GABA upon formation of membrane potential (⌬) (positive inside) but not ⌬pH. VIAAT-mediated GABA uptake had an absolute requirement for Cl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 26 publications
1
67
1
1
Order By: Relevance
“…In addition, acidification of GABAergic SVs must precede GABA uptake (i.e., protonation of the luminal side of VGAT is required for its activation). Such observations are in good agreement with earlier biochemical studies of GABA uptake into isolated SVs (9) that suggested a pivotal contribution of ΔpH on GABA transport and argue against an alternative model of ΔΨ-driven GABA/2Cl -cotransport (13). The latter mode of coupling seems unlikely in intact SVs, because Cl -entry coupled to GABA transport would promote acidification by dissipating ΔΨ (38).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, acidification of GABAergic SVs must precede GABA uptake (i.e., protonation of the luminal side of VGAT is required for its activation). Such observations are in good agreement with earlier biochemical studies of GABA uptake into isolated SVs (9) that suggested a pivotal contribution of ΔpH on GABA transport and argue against an alternative model of ΔΨ-driven GABA/2Cl -cotransport (13). The latter mode of coupling seems unlikely in intact SVs, because Cl -entry coupled to GABA transport would promote acidification by dissipating ΔΨ (38).…”
Section: Discussionsupporting
confidence: 80%
“…We hypothesized that SV refilling with GABA, which has been proposed to occur through a GABA/H + exchange (9) (ref. 13 shows an alternative model), may underlie the observed SV alkalization. To address this hypothesis, we monitored the pH of SVs from VGAT-deficient neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under similar assay conditions, VGAT that is known to cotransport 2 Cl Ϫ and GABA (17), took up radiolabeled Cl Ϫ in the presence of GABA (Fig. 4B) (17). Furthermore, only the background level of Cl Ϫ uptake was observed by NPT1-containing proteoliposomes entrapped with PAH at 1 mM (data not shown).…”
Section: Npt1 Is a CLmentioning
confidence: 79%
“…2B). We then tested whether Cl Ϫ protected DIDS-mediated inactivation because Cl Ϫ competes with DIDS in VGLUT, suggesting the same binding site(s) for Cl Ϫ and DIDS (12,16,17). We found that DIDS strongly inhibited ⌬-dependent PAH uptake with an ID 50 of 5 M (Fig.…”
Section: Npt1 Is a CLmentioning
confidence: 99%